Posttraumatic Stress Disorder (PTSD) and its influence on the Social Life of Victims of Armed Violent Conflict in Kumbo Municipality Resident in Bamenda Municipality, Cameroon - Siver Kibuh; Sigala Maxwell Fokum (Researchparks Publishing, 2022)
Psychological distress from violence is harmful and the victims may experience a sense of helplessness and despair leading to posttraumatic stress disorder (PTSD). This study was designed to investigate how PTSD influence the social life of victims of armed violent conflict in Kumbo Municipality resident in Bamenda Municipalities. Specifically, the study was out to investigate how avoidance, flashbacks, panic attacks influence the social life of victims of armed violent conflict in Kumbo Municipality resident in Bamenda Municipalities. The study adopts a survey research design. Questionnaire and interview guide were used to collect data from internally displaced persons. The sample population of the study was made up of 152 internally displaced persons (IDPs) who are victims of the armed violent conflict from Kumbo resident in Bamenda Municipalities. The IDPs were selected using the purposive and snowball sampling techniques. The instrument used for data collection was a self-constructed questionnaire and interview guide with the reliability of 0.948. Data were analyzed using descriptive and inferential statistical tools. The findings showed that avoidance significantly influences the social life of victims of the armed violent conflict (r= 0.222**, P=0.006, < 0.05). Findings equally affirmed that flashbacks significantly influence the social life of victims (r= -0.193*, P=0.018, < 0.05). Similarly, the findings equally revealed that panic attacks significantly influence the social life of victims (r= -0.354**, P=0.000, < 0.05). The findings indicated that Posttraumatic Stress Disorder negatively affects the social life of victims of the armed violent conflict in Kumbo Municipality resident in Bamenda Municipalities. Based on the findings, some recommendations were made that victims should be given counselling on how to do self-rehabilitation and healing such as making more efforts to avoid thoughts, feelings, or conversations and flashbacks about the traumatic event, actively trying to avoid places or people that remind them of the traumatic events and keeping themselves too busy to have time to think about the traumatic events.